The Role of Deubiquitinases in Virus Replication and Host Innate Immune Response - Zhang, Qinglin; Jia, Qizhen; Gao, Wenying; Zhang, Wenyan (Frontiers in Microbiology, 2022)
As a critical post-translational modification, ubiquitination is known to affect almost all the cellular processes including immunity, signaling pathways, cell death, cancer development, and viral infection by controlling protein stability. Deubiquitinases (DUBs) cleave ubiquitin from proteins and reverse the process of ubiquitination. Thus, DUBs play an important role in the deubiquitination process and serve as therapeutic targets for various diseases. DUBs are found in eukaryotes, bacteria, and viruses and influence various biological processes. Here, we summarize recent findings on the function of DUBs in modulating viral infection, the mechanism by which viral DUBs regulate host innate immune response, and highlight those DUBs that have recently been discovered as antiviral therapeutic targets.